Genes, genesis and God Radio interview with Charles Heyman (Radio National - Australia) - Rolston, Holmes, 1932-2025, speaker; Heyman, Charles, speaker; Australian National Radio, producer (Colorado State University. Libraries, 2003)
Global warming is a bigger threat to the world than Saddam Hussein. Or so says a very distinguished voice - that of Professor Holmes Rolston the third - winner of the latest Templeton Prize - worth nearly two million Australian dollars. The Award is made for raising awareness of how scientific research can lead to discoveries about spirituality.
Breakfast - Australia, broadcast interview with Dr. Rolston Holmes
Charles Heyman interviews Dr. Rolston Australian National Radio on March 26, 2003.
Accessibility features: Unedited transcript.
To request an edited transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: religion; Rolston, Holmes, 1932-2025; Templeton Prize; philosophy professor; science; Colorado State University; environmental ethics